2003
DOI: 10.1063/1.1619355
|View full text |Cite
|
Sign up to set email alerts
|

Kr–Cl stretching vibration of HKrCl: Matrix-isolation and anharmonic ab initio study

Abstract: The Kr–Cl stretching vibration of HKrCl molecule is studied. The absorption shows Cl35 and Cl37 isotopic splitting due to natural abundance of the Cl isotopes. The observed Kr–Cl stretching vibrations of the HKrCl are at 253.1 (35Cl) and 248.3 cm−1 (37Cl). Experimentally, deuteration of the HKrCl does not cause a shift of the Kr–Cl stretching frequency. In addition to the Kr–Cl stretching mode, the bending mode of DKrCl is observed at 397.7 cm−1. The vibrational analysis suggests that the Kr–Cl bond shows some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…HKrCl is one of the noble-gas hydrides thoroughly studied in matrix-isolation experiments. This molecule is formed during 193 nm photolysis of HCl/Kr matrices, evidencing the locality of solid-state photodissociation . The main formation of HKrCl occurs upon consequent annealing at about 30 K, which shows a significant kinetic H/D isotope effect attributed to different thermal mobility of H and D atoms in solid krypton .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HKrCl is one of the noble-gas hydrides thoroughly studied in matrix-isolation experiments. This molecule is formed during 193 nm photolysis of HCl/Kr matrices, evidencing the locality of solid-state photodissociation . The main formation of HKrCl occurs upon consequent annealing at about 30 K, which shows a significant kinetic H/D isotope effect attributed to different thermal mobility of H and D atoms in solid krypton .…”
Section: Introductionmentioning
confidence: 99%
“…The main formation of HKrCl occurs upon consequent annealing at about 30 K, which shows a significant kinetic H/D isotope effect attributed to different thermal mobility of H and D atoms in solid krypton . HKrCl is one of the few noble-gas hydrides, for which all fundamental modes have been observed in the IR spectra …”
Section: Introductionmentioning
confidence: 99%
“…It must be noted that, in Table , a number of double-ζ optimized geometries were excluded because the frequency analysis provided imaginary normal modes, which indicated that the structures found were not minimum energy structures. This was not surprising, as a double-ζ basis set did not correctly predict KrF 2 and HKrCl to be stable with respect to dissociation. , However, both KrF 2 and HKrCl have been shown by experiment to exist ,, and have been shown by computation to be stable when more flexible basis sets (at least aug-cc-pVTZ quality) were used. These previous studies 40,41 suggest that smaller basis sets such as cc-pVDZ are inadequate for the description of krypton-bonded systems.…”
Section: Resultsmentioning
confidence: 99%